ASAS KESETARAAN DALAM AKAD PEMBIAYAAN MUSYARAKAH PADA BANK SYARIAH DI YOGYAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This study focuses on musharaka financings equity principle that has not been fully carried out. The banks do not state explicitly their obligation to share risk and losses and they have set revenue projections beforehand. These eventually blur the profit-loss sharing mechanism thus making the system resembles conventional banks.